2018
DOI: 10.1186/s12860-018-0162-3
|View full text |Cite
|
Sign up to set email alerts
|

Establishment and comparison of air-liquid interface culture systems for primary and immortalized swine tracheal epithelial cells

Abstract: BackgroundAir-liquid interface (Ali) systems allow the establishment of a culture environment more representative of that in vivo than other culture systems. They are useful for performing mechanistic studies of respiratory epithelial cells as drug permeation barriers and can be used to study the interactions between hosts and respiratory pathogens. However, there have been few studies concerning Ali cultures of primary swine tracheal epithelial cells (STECs) and an immortalized STEC line, and the differences … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
36
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(36 citation statements)
references
References 26 publications
0
36
0
Order By: Relevance
“…In our previous study, primary PTECs were isolated for air-liquid interface culture by placing small tracheal tissues digested in a pronase/DNase solution at 2-8 °C overnight for 24 to 48 h [35]; however, in this study, to isolate primary PTECs, isolated tracheal tissues were digested with collagenase I and trypsin together for no more than 1 h. The shorter digestion time of minced porcine tracheal tissues with microsurgical forceps as well as microsurgical scissors allowed a large quantity of extremely pure and reliable epithelial cells. Digestion in this manner with a shorter time has obvious advantages over isolation techniques applied in other species, including animals and human [13,23,36], since an extended digestion time such as 16-48 h and weak enzymes may increase the possibility of other contaminating cells not of epithelial origin [5].…”
Section: Discussionmentioning
confidence: 99%
“…In our previous study, primary PTECs were isolated for air-liquid interface culture by placing small tracheal tissues digested in a pronase/DNase solution at 2-8 °C overnight for 24 to 48 h [35]; however, in this study, to isolate primary PTECs, isolated tracheal tissues were digested with collagenase I and trypsin together for no more than 1 h. The shorter digestion time of minced porcine tracheal tissues with microsurgical forceps as well as microsurgical scissors allowed a large quantity of extremely pure and reliable epithelial cells. Digestion in this manner with a shorter time has obvious advantages over isolation techniques applied in other species, including animals and human [13,23,36], since an extended digestion time such as 16-48 h and weak enzymes may increase the possibility of other contaminating cells not of epithelial origin [5].…”
Section: Discussionmentioning
confidence: 99%
“…2A). Firstly, we investigated the integrity of mucociliary differentiated HBECs grown on Transwell inserts by the measurement of transepithelial electrical resistance (TEER) [31,32] before EMTU establishment. The TEER value was measured again in triplicates in each insert containing differentiated HBECs cultured in the presence of HBFs (in the EMTU) for 4 days.…”
Section: Emtu Cultures From Asthmatics Are More Sensitive To the Tgf-mentioning
confidence: 99%
“…presented in our study revealed more enhanced sensitivity to the TGF-β1 of the AS co-cultures than in case of the NA ones. Measurement of TEER determines the quality of differentiated pseudostratified airway epithelium with well-developed tight junctions and is often used as a marker of a barrier function of the epithelium [31,32,43,44]. However, differences in the TEER values between ALI monocultures of asthmatic and non-asthmatic HBECs remains contradictory.…”
Section: Comparison Of the Compatible Asthmatic Emtu Cultures With Thmentioning
confidence: 99%
See 1 more Smart Citation
“…Such systems may employ perfusion or direct mechanical actuation to stimulate a 3-D construct [12,[15][16][17][18][19], where the method of delivering stimulus and system design are determined by model and application specific requirements [20,21]. Several strategies for respiratory tissue engineering have been described, including decellularized ECM scaffolds [22][23][24], air-liquid interface well inserts [25][26][27] and PDMS microfluidic chips with integrated 2-D membranes [27][28][29]. However, biologically-derived materials introduce batch-batch inconsistencies and there exists a need for a truly 3-D in vitro culture model that also provides mechanical stimuli.…”
Section: Introductionmentioning
confidence: 99%